USE OF RAPID METHODS FOR TESTING MEAT, VISCERA AND ANIMAL PRODUCTS - A. V. Tyunev; M. V. Alekseyeva (Ветеринария сегодня)
Rapid methods of testing are widely used in current laboratory practice. They enable to perform the analysis of animal raw materials and animal products much faster in comparison with classical methods. Different methods of rapid diagnosis were evaluated, and identification of Salmonella, Listeria monocytogenes, coliforms, QMAFAnM was performed. The following methods of analysis were used: fluorescent analysis, enzyme linked fluorescent assay (ELFA), and immunochromatographic assay. TEMPO® BMerieux system was used for quantitative determination of QMAFAnM and coliforms; VIDAS and miniVIDAS instruments were used for the diagnosis of Salmonella and Listeria monocytogenes; immunochromatographic test-systems Singlepath were also used. All the used rapid methods have demonstrated high accuracy and specificity, they allow to shorten test time, and their results were confirmed by classical microbiological tests. 100 positive confirmed results were obtained from testing beef samples (10.8% of the total number of tests performed). 53 positive results were obtained in rapid test (confirmed by classical test), which makes 20.37% of the total number of tests performed. 56 positive confirmed results were obtained from testing cattle viscera using classical tests (12.6%). 13 samples tested positive using rapid test (13%). The used rapid tests are timesaving, demonstrate high accuracy and specificity, enable to trace measurements; tools are easy to use and maintain, and reagents have a long shelf life.